2022
DOI: 10.1021/acsomega.2c01679
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Iron Complexes of Tannic Acid and Other Related Polyphenols as Revealed by Spectroscopic Techniques: Implications in the Identification and Characterization of Iron Gall Inks in Historical Manuscripts

Abstract: In this work, a structural analysis of the polyphenol complexes with iron and copper at several conditions is reported. The investigated polyphenols were tannic acid, gallic acid, pyrogallol, and syringic acid, being components and molecular models of the gallnuts usually employed in the past in fabrication of iron gall inks (IGIs). Commercial tannic acid extracted from gallnuts, which is a complex mixture of different gallotannins and simpler galloylglucoses, was also employed in this analysis. This analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…The similar sizes of FTCNs-2 and FTCNs-3 are likely due to the presence of more Fe 3+ , which may also increase the particle size by extensive cross-linking, consistent with TGA data showing the increase of iron content from FTCNs-1 to FTCNs-3 (6.47, 7.31, and 9.16%, respectively) (Figure D). According to previous work, , the peaks around 550 cm –1 from Raman spectra indicate the coordination bonding between Fe 3+ and TA (Figure E). Other peaks around 1457 and 1519 cm –1 are attributed to the stretching mode of gallic benzene ring, and those around 850 cm –1 are assigned to the −CH deformation (Figure E).…”
Section: Resultssupporting
confidence: 73%
“…The similar sizes of FTCNs-2 and FTCNs-3 are likely due to the presence of more Fe 3+ , which may also increase the particle size by extensive cross-linking, consistent with TGA data showing the increase of iron content from FTCNs-1 to FTCNs-3 (6.47, 7.31, and 9.16%, respectively) (Figure D). According to previous work, , the peaks around 550 cm –1 from Raman spectra indicate the coordination bonding between Fe 3+ and TA (Figure E). Other peaks around 1457 and 1519 cm –1 are attributed to the stretching mode of gallic benzene ring, and those around 850 cm –1 are assigned to the −CH deformation (Figure E).…”
Section: Resultssupporting
confidence: 73%
“…Thus, the electron density of the conjugate system is reduced, which increases the bond order of the C�C bonds in the aromatic ring, and leads to a more intense υ 2 band. 51 Our findings reveal that the binding strength of the Ti IV −TA complexes enhances, thereby improving the stability of the urea−MPN matrix. SEM analyses of TA, ground urea, and urea−MPN matrix indicated that both TA and urea crystals underwent shape restructuring after coordination with Ti IV metal ions during the MPN assembly (Figure 1f−h).…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…various spectroscopic techniques such as Raman, Fourier-transformed infrared (FTIR), UV-Vis absorption, and uorescence spectroscopy [17]. Haskovic and Ibragic used XRF and FTIR techniques for the detection of inks and pigments in manuscripts [15].…”
Section: Espina Et Al Studied To Determine the Characterization Of Ir...mentioning
confidence: 99%
“…Later, black inks obtained from ivory and bone were used. In addition to these inks used, iron-gall inks used by the Late Roman Empire in the west until the 19th century and even the 20th century were the primary choices for the creation of many manuscripts [14,[16][17][18][19][20]. It is known that the expression gallotannate, which indicates iron-gall ink, was used in Pliny's book in the 1 s t century AD [14,16,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation